Langerhans cell sarcoma of the vulva: Case report and review of the literature - Stephanie Tillit; Semiramis Carbajal-Mamani; Robert Zlotecki; Li-Jun Yang; Ashwini Esnakula; Jacqueline Castagno; Joel Cardenas-Goicoechea (Gynecologic Oncology Reports, 2020)
Langerhans cell sarcoma (LCS) is a rare, malignant neoplastic disorder of Langerhans cells thought to arise from antecedent Langerhans cell histiocytosis (LCH) or de novo. There are less than 70 cases of LCS reported in the medical literature, with this case being the first report of primary vulvar LCS. We present the case of a 73-year-old female with a painful 2 cm ulcerated lesion of the right labia majora. The patient was treated with oral antibiotics without resolution. On referral to gynecologic oncology an office biopsy showed LCS. Surgical excision was performed with clear margins and diagnostic confirmation of LCS by histopathological features and immunohistochemical evaluation. The patient received adjuvant radiation therapy (45.6 Gy). After 33 months of surveillance, the patient remains with no evidence of disease. Due to the rarity of this disease, there is a lack of standardized recommendations for adjuvant therapy, including radiotherapy and chemotherapy regimens for both localized and systemic LCS. This case report supports the management of localized disease by surgical excision followed by radiotherapy as effective for preventing recurrence and metastatic progression. Early recognition and treatment are critical for cure, and can be accomplished by prompt referral to a specialist as well as low threshold for biopsy. Further investigation is needed for establishing a standardized management guideline for LCS.